Optimizing Online Police Clearance Certificate Services: Empirical Legal Analysis of Digital Public Service Innovation - Gede Adhi Arya Wiryanatha; Halimah Halimah; Sutrisno Sutrisno; Yudhi Hery Setiawan (Realism: Law Review, 2026)
This study aims to analyze the implementation of the online Police Clearance Certificate (SKCK) service as a digital innovation in public service at the Administrative Service Section (Si Yanmin) of the Intelligence and Security Directorate, Central Kalimantan Regional Police. The background of this study is based on the increasing demand for public services that are efficient, transparent, and responsive in the digital era. This research is an empirical legal research that employs a qualitative approach using in-depth interviews, observation, and documentation as data collection techniques. The findings indicate that the implementation of the online SKCK service has improved service responsiveness through faster processing time, enhanced efficiency by simplifying administrative procedures, and strengthened accountability and transparency through an integrated digital system. From the perspective of innovation diffusion theory, the service demonstrates a relatively high level of adoption, as most users prefer the online system due to its practicality and efficiency. However, several challenges remain, including system and network instability, limited digital literacy among users, and constraints in human resources. This study concludes that the online SKCK service is operationally effective but remains in a consolidation stage toward achieving a more stable, inclusive, and fully optimized digital public service.